Influence of size and shape on optical properties of cesium tungsten bronze: An experimental and theoretical approach. Issue 5 (1st March 2022) - Chao, Luomeng; Sun, Changwei; Li, Jiaxin; Sun, Miao; Liu, Jia; Ma, Yonghong
Abstract: Although the optical properties of nanocrystalline cesium tungsten bronze have been widely studied, there is a lack of research on the effect of particle size on its optical properties. In order to further investigate size and shape effect on the NIR shielding performance, cesium tungsten bronze nanoparticles with different sizes and morphologies were prepared by two methods. The size of irregular shaped samples prepared by solvothermal method is tens of nanometers, while the size of hexagonal prism shaped samples prepared by solid state reaction method is hundreds of nanometers. The element spectrums shows that there are more oxygen vacancies in large particles than in small particles. The NIR shielding performance of large particles far lower than that of small particles, indicating that the influence of shape and size on optical properties is more obvious than that of oxygen vacancy. Theoretical calculation on hexagonal prism shaped particles exhibits that the NIR extinction of large aspect ratio is better at longer wavelength and small aspect ratio is better at shorter wavelength.